Internal Democratization of Political Parties and Limitation of the Power of the General Chairperson in the Indonesian Party System - Kurniawan, Hendrik; Susilo, Wendari Iga (Jurnal El-Thawalib, 2026)
The dominance of political party chairmen in the process of formulating public policy in Indonesia indicates a serious problem in democratic practices. The common fact that every draft law discussed in parliament must be approved by the party chairmen indicates an excessive centralization of power in the hands of political party chairmen. This condition creates a paradox, where political parties, as a means of articulating and aggregating public interests, actually become instruments of the interests of a handful of elite parties. This study aims to determine the level of democracy within political parties and examine how to constitutionally limit the term of office of political party chairmen. This study uses a normative legal research method with a statute approach. The legal sources used are primary legal sources, namely legal materials that include provisions of applicable laws and regulations and secondary legal materials that support primary legal sources, namely scientific journals related to public office and justice. Data collection techniques use legal interpretation and are analyzed using analytical descriptive techniques. The results of this study indicate that the general chairperson of a political party still holds absolute power without adequate control mechanisms, including the absence of term limits which allows for the emergence of a prolonged political oligarchy. Reconstruction of the political party system can be carried out by conducting a judicial review of Article 23 paragraph (1) of the political party law or by revising the political party law organically through the legislative body